Sistem Peringatan Dini Bencana Longsor Menggunakan Sensor Accelerometer dan Sensor Kelembabapan Tanah Berbasis Android - Onny Octaviani Artha; Budi Rahmadya; Rahmi Eka Putri (JITCE (Journal of Information Technology and Computer Engineering), 2018)
Landslide is one of the most frequent disasters in Indonesia, especially in hilly areas, valleys, and volcanoes. Geographical conditions that are generally mountainous areas and have slopes make the soil unstable. As a result, when the movement of the land becomes easy to slide. Ground shifts and excessive water content are the main causes of landslides. The landslide disaster can cause many losses, such as to cause loss of life, can disrupt transportation facilities, damage agricultural land, and various other consequences. In this study used sensor MPU6050 and Soil Moisture and NodeMcu sensors to provide early warning of landslides. Linear acceleration is detected by using MPU6050 sensor and will define the ground movement based on the scenarios developed in this study. Soil moisture sensor detects soil moisture. The result of soil movement detection and soil moisture is stored in file storage. When ground detection and soil moisture is greater than 51%, the alarm alert is sent to the user's smartphone with a 100% success percentage.